The Development of Terminal Bus Kampung Rambutan in East Jakarta with Art Deco Style - Randy Afriandi (Jurnal Desain, 2016)
The purpose of this paper is the realization of the concept of space into a form of human activity through technology approach that is more directed to the physical building, so the transportation building is expected to fully functional as a public space. The Design method are by conducts field surveys, sketches ideas / concepts, drafts the floor plans, elevates, section and the development of three-dimensional design. Public transport infrastructure facilities is a fundamental requirement of economic activities of DKI Jakarta. Transportation which is fast, inexpensive, and convenient has been an absolute necessity for the city of Jakarta. Bus station which also serves as a transfer is part of the concept of the provision of public transport. Bus station as a 'public reception room' in a city would be expected to have adequate infrastructure and equipped spatial comfortable, and clean.